2015
DOI: 10.1371/journal.pone.0125112
|View full text |Cite
|
Sign up to set email alerts
|

Altered Activation of Innate Immunity Associates with White Matter Volume and Diffusion in First-Episode Psychosis

Abstract: First-episode psychosis (FEP) is associated with inflammatory and brain structural changes, but few studies have investigated whether systemic inflammation associates with brain structural changes in FEP. Thirty-seven FEP patients (median 27 days on antipsychotic medication), and 19 matched controls were recruited. Serum levels of 38 chemokines and cytokines, and cardiovascular risk markers were measured at baseline and 2 months later. We collected T1- and diffusion-weighted MRIs with a 3 T scanner from the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 110 publications
(122 reference statements)
0
21
0
Order By: Relevance
“…Further studies are required that com- pare untreated depressed patients with healthy subjects, in order for it to be stated that MDC is a suitable marker of MDD/BP. Mäntylä et al [29] also found changes in the MDC levels of first-episode psychosis, which could be negatively correlated with white matter volume within specific frontal regions of interest (ROIs), and positively with mean diffusivity and radial diffusivity bilaterally in the frontal lobes in ROI analyses. With regard to treatment response in schizophrenic patients, in the study by Ramsey et al [27] , MDC levels were significantly elevated with a sex-specific effect after 6 weeks of antipsychotic treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Further studies are required that com- pare untreated depressed patients with healthy subjects, in order for it to be stated that MDC is a suitable marker of MDD/BP. Mäntylä et al [29] also found changes in the MDC levels of first-episode psychosis, which could be negatively correlated with white matter volume within specific frontal regions of interest (ROIs), and positively with mean diffusivity and radial diffusivity bilaterally in the frontal lobes in ROI analyses. With regard to treatment response in schizophrenic patients, in the study by Ramsey et al [27] , MDC levels were significantly elevated with a sex-specific effect after 6 weeks of antipsychotic treatment.…”
Section: Discussionmentioning
confidence: 96%
“…The patients participating in the Helsinki Psychosis Study (Keinänen et al, 2015;Mäntylä et al, 2015;Raij et al, 2015;Rikandi et al, 2017) were aged 18-40, with first psychiatric treatment contact for psychosis in hospitals and outpatient clinics of the City of Helsinki and Helsinki University Hospital between December 2010 and July 2016. As a criterion for inclusion, we defined psychosis as a score of at least 4 in the items assessing unusual thought content (delusions) or hallucinations in the Brief Psychiatric Rating Scale, Expanded version 4.0, BPRS (Ventura et al, 1993), corresponding to mild but definite delusions or hallucinations.…”
Section: Participants and Study Proceduresmentioning
confidence: 99%
“…For the PET study, fasting serum was sampled before radiotracer injection at 8-9 a.m. on the day of PET. The HEPS sample included 34 patients and 17 controls from our previous report 17 , but we used unthawed serum samples from these participants and reanalyzed them as a part of the current project.…”
Section: Laboratory Analytical Methodsmentioning
confidence: 99%
“…Associating TSPO tracer V T to auxiliary immune parameters, such as cyto/ chemokine networks, have been suggested to facilitate the interpretation of the source and functional association of variation in TSPO V T 10 . We have previously studied a panel of 38 cytokines and chemokines in patients with first-episode psychosis (FEP) and healthy controls, and found elevated serum chemokine CCL22 levels associating with white matter volume and diffusion in FEP patients 17 . Here, we used two Finnish cohorts of FEP patients and matched controls to study (a) differences in serum cytokine and chemokine levels in FEP patients and controls, (b) the role of potential confounding factors, namely age, sex, smoking, cannabis use, body mass index (BMI), and antipsychotic medication type, duration, and dose, (c) the persistence of any changes during one-year follow-up, and (d) the relationship between the observed changes and clinical characteristics such as the severity of symptoms and achieving remission in the one-year follow-up.…”
Section: Introductionmentioning
confidence: 99%